The Pine Branch, November 1931 - (:unkn) unknown (Valdosta, Ga. : Writers Club of the Georgia State Womans College., 1931)
This periodical contains several pieces written by various members of the Writer's Club. There are several short stories, poems, and an editorial on Thanksgiving. Additionally there are a number of advertisements from local Valdosta businesses at the end of the publication.
A Thanksgiving -- Clouds -- Gigolo Hats -- White Circles -- Resurrection --On the Consumption of Grapefruit -- Thwarted Moments -- Smiling Pictures -- Editorial -- Critical Tips -- Locals -- Clubs -- Y.W.C.A. -- Societies -- Athletics -- Alumnae -- Jokes
Keywords: College publications; College student newspapers and periodicals; Valdosta State University--Periodicals; Women; Women's colleges--Georgia--Valdosta; Georgia State Womans College; Valdosta; Schools--Georgia; Education